A Comparison of Nine Primocane Fruiting Raspberry Cultivars for Suitability to a High-Elevation, Arid Climate. Issue 1 (1st January 2021) - Hansen, Sheriden; Black, Brent; Alston, Diane; Lindstrom, Thor; Olsen, Shawn
ABSTRACT: A replicated trial, planted in 2011, compared nine primocane-fruiting raspberry cultivars for suitability to commercial production in the U.S. Intermountain West. Factors evaluated included annual yield, fruit size, fruiting season, consumer preference, leaf chlorophyll content, and cane infestation by raspberry horntail, a common insect pest of raspberries in northern Utah. 'Joan J' was the highest yielding cultivar, averaging 3.32 kg per row meter, followed by 'Polana', 'Autumn Bliss', and 'Dinkum' with 2.53, 2.01, and 1.34 kg·m −1, respectively. 'Autumn Bliss' and 'Joan J' were the earliest to fruit with a harvest midpoint 4 and 2 days before 'Polana', respectively. Leaf chlorophyll concentration (CCl) was highest in 'Joan J' and 'Autumn Treasure', averaging 30.9 and 27.0 CCl, respectively. All cultivars exhibited similar susceptibility to raspberry horntail, with differences in infestation rates related to the location in the field. A survey of farmers' market customers found the highest consumer preference for 'Autumn Bliss', 'Dinkum', and 'Vintage'. Only the earliest cultivars gave commercially viable yields for the high elevation valleys of the Intermountain West region of the U.S.